Development of social network analysis platform - Adnan, Sumayyah; Gunawan, Teddy Surya; Nasir, Haidawati; Kartiwi, Mira (IEEE, 2019)
The social network is a platform where a big number of data can be collected as the number of social network users grows each day. Many data scientists are investigating the correlation of those data collected from different users and different locations on the social network. In this research, a platform is developed to stream the Twitter APIs to study the social network analysis on Twitter. This platform development process will be divided into three process, including extraction, classification and application process. This streaming process will be done using Tweepy, an open source Python library for Twitter API that is used in the Twitter data mining process. The data extracted from this process will later be visualized in a visualization tool for social network analysis. This platform is intentionally created to aid the user to analyze the data extracted from Twitter with a simple application. The sentiment analysis from various tweets will be analyzed using machine learning tool and visualized in graph for better visualization.